Nguyên hàm của hàm số \(f\left( x \right) = {x^2}...

Câu hỏi: Nguyên hàm của hàm số \(f\left( x \right) = {x^2} - 3x + \frac{1}{x}\) là:

A \(\int {f\left( x \right)} dx = \frac{{{x^3}}}{3} + 3\frac{{{x^2}}}{2} + \ln \left| x \right| + C\).

B \(\int {f\left( x \right)} dx = \frac{{{x^3}}}{3} - 3\frac{{{x^2}}}{2} - \ln x + C\)

C \(\int {f\left( x \right)} dx = \frac{{{x^3}}}{3} - 3\frac{{{x^2}}}{2} + \ln \left| x \right| + C\).

D \(\int {f\left( x \right)} dx = \frac{{{x^3}}}{3} - 3\frac{{{x^2}}}{2} - \ln \left| x \right| + C\).